The Creative History Teacher as A Creative Historian - Supriatna, Nana (History Department, Semarang State University and Historian Society of Indonesia, 2021)
This article included the author’s analysis results which referred to the history learning process findings in schools and the theoretical aspects of creativity regarding creative history teachers. The author made an analogy for a creative history teacher as a creative historian. The paper combined two different approaches in the History education field and in cognitive psychology. The first approach used cognitive aspects of thinking developed by Vygotsky related to the ability of imagination. The second approach used the historical method from Collingwood in interpreting historical data and facts that also used imagination. The first approach analyzed how history produces creative history learning to cultivate students’ creative thinking abilities. At the same time, the second approach resulted from creative historiography as a historian’s creative work, which can also be seen in history textbooks for history subjects in schools. Both approaches that seem classic lead to creative thinking skills, both for history teachers and historians, including history textbook writers. Both approaches are also enriched with contemporary theoretical aspects, especially in the pedagogical aspect. This article focused on several history teachers who teach at senior high schools in Bandung. Some are also students of the Master Program in History Education, Graduate School of the Indonesia University of Education (UPI). They were used as resource persons through dialogue and observation and the Field Experience Program (PPL) implementation for prospective History teachers.Artikel ini berisi hasil analisis penulis yang mengacu pada temuan proses pembelajaran Sejarah di sekolah dan juga mengacu pada aspek teoretis kreativitas mengenai guru Sejarah kreatif. Penulis menganalogikan guru Sejarah kreatif sebagai sejarawan kreatif. Tulisan memadukan dua pendekatan berbeda dalam bidang pendidikan Sejarah dan dalam psikologi kognitif. Pendekatan pertama menggunakan aspek kognitif dalam berpikir yang dikembangkan oleh Vygotsky terkait dengan kemampuan imajinasi. Pendekatan kedua menggunakan metode kesejarahan dari Collingwood dalam menafsir data dan fakta peristiwa Sejarah yang juga menggunakan imajinasi. Pendekatan pertama digunakan untuk menganalisis bagaimana Sejarah menghasilkan pembelajaran Sejarah yang kreatif dengan tujuan menghasilkan kemampuan berpikir kreatif peserta didik. Sedangkan pendekatan kedua menghasilkan historiografi kreatif sebagai karya kreatif sejarawan yang juga bisa nampak pada buku teks Sejarah untuk Pelajaran Sejarah di sekolah. Kedua pendekatan yang nampaknya klasik tersebut bermuara pada menghasilkan kemampuan berpikir kreatif, baik berpikir guru Sejarah maupun berpikir sejarawan, termasuk penulis buku teks Sejarah. Kedua pendekatan tersebut juga diperkaya dengan aspek teoretis kontemporer, khususnya dalam aspek pedagogik. Tulisan difokuskan pada beberapa guru Sejarah yang mengajar di SMA di Bandung. Sebagian dari mereka adalah juga sebagai mahasiswa Program Magister Pendidikan Sejarah, Sekolah Pascasarjana Universitas Pendidikan Indonesia (UPI). Mereka dijadikan narasumber melalui dialog dan observasi bersamaan dengan pelaksanaan Program Pengalaman Lapangan (PPL) calon guru Sejarah.